2014
DOI: 10.1002/jcp.24823
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hedgehog Agonists Promote Osteoblast Differentiation in Mesenchymal Stem Cells

Abstract: Hedgehog (Hh) family members are involved in multiple cellular processes including proliferation, migration, differentiation, and cell fate determination. Recently, the novel Hh agonists Hh-Ag 1.3 and 1.7 were identified in a high-throughput screening of small molecule compounds that activate the expression of Gli1, a target of Hh signaling. This study demonstrates that Hh-Ag 1.3 and 1.7 strongly activate the expression of endogenous Gli1 and promote osteoblast differentiation in the mesenchymal stem cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…In addition, appropriate osteoblast calcification or bone mineralization is essential for complete bone formation (13)(14)(15). The process of bone regeneration has the potential to treat defects in bone healing in patients with osteoporosis with bone fractures or abnormalities in osteogenesis (9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, appropriate osteoblast calcification or bone mineralization is essential for complete bone formation (13)(14)(15). The process of bone regeneration has the potential to treat defects in bone healing in patients with osteoporosis with bone fractures or abnormalities in osteogenesis (9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…During skeletal development, Runx2 regulates Osterix expression at an early stage of osteoblast differentiation, due to crosstalk between the Wnt, IHH and FGF signalling pathways . Indeed, Osterix expression was absent in Runx2‐deficient mice; as it seems, Osterix functioned downstream of Runx2 during osteoblast differentiation and Wnt signalling is required for progression from the Runx2 + stage to the Runx2 + Osterix + stage, and then, to the mature osteoblast stage . However, Runx2 also promotes osteoclastogenesis and bone resorption in some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large number of studies have shown that TGF-β plays a pivotal role in bone regeneration and is involved in the formation and growth of bone during embryogenesis [ 25 ]. During the early stages of bone formation in newborns, TGF-β1 and TGF-β2 in particular are expressed in the cartilage and periosteum, and TGF-β1 has been shown to promote the proliferation and differentiation of mesenchymal cells into mature bone cells in these tissues [ 26 ]. Mechanistically, TGF-β1 mainly functions to regulate the transcription and activity of genes essential for mesenchymal cell differentiation in addition to promoting the synthesis of extracellular matrix (ECM) and ECM associated proteins (e.g., collagen, osteonectin, and osteopontin) and increasing the rate of bone matrix deposition [ 27 ].…”
Section: Discussionmentioning
confidence: 99%